The use of indocyanine green angiography in postmastectomy reconstruction: Do outcomes improve over time?. Issue 4 (April 2019) - Diep, Gustave K.; Marmor, Schelomo; Kizy, Scott; Huang, Jing Li; Jensen, Eric H.; Portschy, Pamela; Cunningham, Bruce; Choudry, Umar; Tuttle, Todd M.; Hui, Jane Yuet Ching
Summary: Background: Indocyanine green angiography (ICGA) reduces ischemic complications by assessing mastectomy flap perfusion intraoperatively. However, outcomes of ICGA can be surgeon-dependent due to its relative novelty. We aimed to determine whether patient outcomes improved with the adoption of ICGA over time. Methods: We conducted a single-institution retrospective study of mastectomy patients between March 2012 (date of ICGA introduction) and October 2016. We included patients who underwent immediate expander-based reconstruction with intraoperative ICGA, followed by second-stage permanent implant placement. Patients were chronologically sorted into 3 groups, of 45 patients each, based on the date of ICGA. Complications and reconstruction wait times (time between initial expander placement and subsequent final reconstruction) amongst the 3 groups were evaluated. Using the Cochran–Armitage test for trend, we tested the change in median adjusted expander fill volumes (expander fill volume in milliliter per gram of breast removed) over time. Results: We identified 135 patients. Rates of ischemic complications significantly decreased (Group 1, 36%; Group 2, 22%; Group 3, 11%; p  = 0.03), despite significantly increasing median adjusted expander fill volumes (Group 1, 0.46 mL/g; Group 2, 0.63 mL/g; Group 3, 0.76 mL/g; p  = 0.003) over time. The rates of unexpected returns to the operating room across the 3 groups were not significantly different. The median reconstruction wait time was significantly reduced in the later groups (Group 1, 146 days; Group 2, 122 days; Group 3, 87 days; p  = 0.01). Conclusions: Outcomes for mastectomy with immediate expander-based reconstruction were found to improve with increasing case volume after implementation of ICGA.